(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The transformation of the modern economic system is more than obvious and our main objective is to point out the need for the articulation of new organizational forms. In this paper, we use the results of empirical studies published in the literature and theoretical elaboration by using inductive/deductive methods. We believe that a new organization must correspond to human nature, which is based on self-affirmation in the world of labor in which the creativity, imagination, play and cooperation are among the key factors. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.